Workshop on nonstationarity, hydrologic frequency analysis, and water management - Olsen, J. Rolf, editor; Kiang, Julie E., editor; Waskom, R. M. (Reagan McTier), editor; Colorado State University, Colorado Water Institute, publisher (Colorado State University. Libraries, 2010)
An underlying assumption of traditional hydrologic frequency analysis is that climate, and hence the frequency of hydrologic events, is stationary, or unchanging over time. A stationary series is relatively easy to forecast: one simply predicts that statistical properties will be the same in the future as they have been in the past. Anthropogenic climate change and better understanding of decadal and multi-decadal climate variability present a challenge to the validity of this assumption. The workshop held on January 13-15, 2010 in Boulder, Colorado was organized to present and discuss possible operational alternatives to the assumption of stationarity in hydrologic frequency analysis.
Keywords: Hydrologic models -- Congresses; Water resources development -- Congresses; Climatic changes -- Congresses